Preventive negative pressure wound therapy following open ventral hernia repair: A Systematic Review - Adrian; Puji, Sri (International Medical Journal Corp. Ltd, 2024)
Background: Ventral hernia repair (VHR) is a common surgical procedure, but it carries a high risk of wound complications. These complications can significantly impact patient quality of life, increase hospital costs, and raise the risk of hernia recurrence. Negative pressure wound therapy (NPWT) has emerged as a potential solution to reduce these complications, particularly when applied to closed surgical incisions (iNPWT). Methods: A comprehensive literature search was conducted to identify studies comparing iNPWT with standard wound dressings in VHR patients. Data were extracted and synthesized from the included studies to assess the impact of iNPWT on these outcomes. Results: iNPWT significantly reduced the incidence of both SSO and SSI compared to conventional wound dressings. The use of iNPWT did not significantly affect LOS, and no serious adverse effects were reported. Conclusion: iNPWT is effective in reducing postoperative wound complications, particularly SSO and SSI, in patients undergoing open VHR. While the reduction in hernia recurrence was not significant, iNPWT's overall benefits make it a valuable addition to postoperative care. Future research should focus on large, randomized controlled trials to further validate these findings and explore the long-term benefits and cost-effectiveness of iNPWT in diverse patient populations.